Handbook of energy engineering calculations - Hicks, Tyler Gregory, 1921- (New York : McGraw-Hill, 2012)
"SOLVE ENERGY PROBLEMS QUICKLY AND ACCURATELYFilled with step-by-step procedures for performing hundreds of calculations, this practical guide helps you solve a variety of applied energy engineering design and operating problems. Handbook of Energy Engineering Calculations features worked-out examples and enables you to obtain accurately results with minimum time and effort. Calculation procedures emphasize greenhouse gas and carbon dioxide emissions control as well as energy conservation and reuse. This is an invaluable, time-saving resource for anyone involved in energy engineering.Comprehensive coverage includes: Energy conversion engineering Steam power generation Gas-turbine power generation Internal-combustion engine energy analysis Nuclear energy engineering Hydroelectric energy power plants Wind power energy design and application Solar power energy application and usage Geothermal energy engineering Ocean energy engineering Heat transfer and energy conservation Fluid transfer engineering Interior climate control energy economics Energy conservation and environmental pollution control "--Provided by publisher.
"This practical guide helps engineers solve energy problems quickly and accurately using step-by-step procedures for performing more than 500 calculations together with worked out examples and numerical results"--Provided by publisher.
Energy conversion engineering -- Steam power generation -- Gas-turbine energy power generation -- Internal combustion engine energy analyses -- Nuclear energy engineering -- Hydroelectric energy power plants -- Wind-power energy design and applications -- Solar-power energy application and usage -- Geothermal energy engineering -- Ocean energy engineering -- Heat transfer and energy conservation -- Fluid transfer engineering -- Interior climate control energy economics -- Energy conservation and environmental pollution control. power generation Reciprocating-engine power generation Nuclear power generation Renewable energy sources for "green" power generation Sewage and wastewater treatment and re-use in energy options .
Includes index.
0
Keywords: Power (Mechanics) -- Mathematical models -- Handbooks, manuals, etc; Force and energy -- Mathematical models -- Handbooks, manuals, etc; Engineering mathematics -- Formulae -- Handbooks, manuals, etc